2022
DOI: 10.1016/j.jsxm.2022.03.220
|View full text |Cite
|
Sign up to set email alerts
|

Treatments for Persistent Genital Arousal Disorder in Women: A Scoping Review

Abstract: Background Persistent genital arousal disorder (PGAD) is characterized by elevated discomfort associated with persistent genital arousal in the absence of sexual desire. Aim To perform a scoping review of the proposed treatments for PGAD and their efficacy. Methods A scoping review was carried out (PRISMA-Scr) that included articles on PGAD as the main disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Some studies indicate a correlation between the onset of PGAD symptoms and taking or stopping antidepressants including SSRIs [10,11]. In the case we described, the correlation between discontinuation of an antidepressant and the beginning of symptoms and their disappearance when the drugs of this class are re-prescribed is clearly observed.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Some studies indicate a correlation between the onset of PGAD symptoms and taking or stopping antidepressants including SSRIs [10,11]. In the case we described, the correlation between discontinuation of an antidepressant and the beginning of symptoms and their disappearance when the drugs of this class are re-prescribed is clearly observed.…”
Section: Discussionmentioning
confidence: 52%
“…The PGAD studies point to the need to exclude organic pathology of the external genitalia [8,9]. Our patient was under constant observation by a gynecologist for polycystic ovarian syndrome and the gynecologist also excluded pathology of the external genitalia.…”
Section: Discussionmentioning
confidence: 88%
“…However, current evidence suggests that psychological, pharmacological, and physiological treatment approaches may be appropriate and effective (Goldstein et al, 2021 ; Martín-Vivar et al, 2022 ; Pease et al, 2022 ; Pukall et al, 2022 ). A scoping review of proposed treatments for PGAD/GPD (Martín-Vivar et al, 2022 ) identified 38 studies and found evidence for physical treatments such as surgery, neuromodulation, and pelvic floor physiotherapy; pharmacological approaches such as the use of paroxetine, duloxetine, and clonazepam; and psychotherapy approaches such as cognitive-behavior therapy (CBT), couples therapy, mindfulness, and hypnotherapy. Notably, the scoping review only identified seven studies which examined psychological interventions, all of which were case studies.…”
Section: Introductionmentioning
confidence: 99%